Influence of modeling agents on the surface properties of an esthetic nano-hybrid composite - Zeynep Bilge Kutuk; Ecem Erden; Damla Lara Aksahin; Zeynep Elif Durak; Alp Can Dulda (Restorative Dentistry & Endodontics)
ObjectiveThe aim of this study was to evaluate the influence of different modeling agents on the surface microhardness (Vickers hardness number; VHN), roughness (Ra), and color change (ΔE) of a nano-hybrid composite with or without exposure to discoloration by coffee.Materials and MethodsSixty-four cylinder-shaped nano-hybrid composite specimens were prepared using a Teflon mold. The specimens' surfaces were prepared according to the following groups: group 1, no modeling agent; group 2, Modeling Liquid; group 3, a universal adhesive (G-Premio Bond); and group 4, the first step of a 2-step self-adhesive system (OptiBond XTR). Specimens were randomly allocated into 2 groups (n = 8) according to the storage medium (distilled water or coffee). VHN, Ra, and ΔE were measured at 24 hours, 1 week, and 6 weeks. The Kruskal-Wallis test followed by the Bonferroni correction for pairwise comparisons was used for statistical analysis (α = 0.05).ResultsStorage time did not influence the VHN of the nano-hybrid composite in any group (p > 0.05). OptiBond XTR Primer application affected the VHN negatively in all investigated storage medium and time conditions (p < 0.05). Modeling Liquid application yielded improved Ra values for the specimens stored in coffee at each time point (p < 0.05). Modeling Liquid application was associated with the lowest ΔE values in all investigated storage medium and time conditions (p < 0.05).ConclusionDifferent types of modeling agents could affect the surface properties and discoloration of nano-hybrid composites.